Effects of pre-treatment with Aspergillus awamori and extraction methods on essential oil yield from spearmint leaves (Mentha spicata L.) - Yasriza Nanda; Rian Fiqraini; Kelvin Alfianza; Rijanti Rahaju Maulani; Noor Illi Mohamad Puad; Muhammad Yusuf Abduh (Current Research on Bioscences and Biotechnology, 2023)
Extraction of essential oil from spearmint leaves is typically hindered by the presence of cell wall composed of lignocellulose which can be biologically degraded by microorganisms. This study aimed to investigate the effects of fermentation using Aspergillus awamori towards the lignocellulosic content of spearmint (Mentha spicata L.) leaf as well as spearmint oil yield and composition, and diffusion coefficient obtained using different extraction methods. Fermentation of the spearmint leaves were carried out for 3, 6, and 9 days followed by drying and extraction using three different techniques particularly Soxhlet, hydrodistillation and maceration. After fermentation, the cellulose, hemicellulose, and lignin reduced from 37.92% to 19.32%, 13.98% to 5% and 27.20% to 12.24%, respectively. The yield of spearmint oil varies from 0.35% to 2.10% for maceration, 0.22% to 1.83% for Soxhlet and 0.07% to 0.58% for hydrodistillation with a maximum yield (2.10%) was obtained using a maceration method after 9 days of fermentation. The composition of spearmint oil has been determined and contains carvone as the major compound up to 77.88%. In addition, the diffusion coefficients for extraction of spearmint oil using the different extraction methods have been estimated and lies in the range of 2.89 x 10-11 m2/s to 3.64 x 10-11 m2/s. Hence, the fermentation of spearmint leaves using A. awamori decreased the lignocellulose content and thereby increased the yield of spearmint oil. In addition, the composition spearmint oil and diffusion coefficients of the extraction process have been determined.